Method and system for calculating and evaluating hydrogen storage performance of solid hydrogen storage material
The microscopic model of solid nitrogen storage materials was constructed through functional density theory and molecular dynamics methods, and the problems of low nitrogen storage amount and poor kinetic characteristics of solid nitrogen storage materials were solved, achieving more efficient hydrogen adsorption and kinetic performance.
Patent Information
- Application Number
- CN202411286604.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing solid hydrogen storage materials have problems such as low hydrogen storage, difficult hydrogen storage and discharge process, slow dynamics of hydrogen storage and discharge process, and incomplete hydrogen release, which limits the application of solid hydrogen storage.
The material microscopic model was constructed using functional density theory and molecular dynamics method to analyze the mechanical properties, electron distribution, thermal conductivity and thermal stability of the material, and evaluate the hydrogen adsorption performance and kinetic characteristics of the material by calculating the adsorption state and adsorption energy of hydrogen molecules on the hydrogen storage material.
It effectively improves the hydrogen adsorption performance and kinetic characteristics of solid hydrogen storage materials, shortens the R&D cycle of new materials, reduces experimental costs, improves research efficiency, and provides theoretical support and directional guidance for subsequent experiments.
Smart Images

Figure CN119517211A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen storage performance calculation and evaluation, and in particular to a method and system for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material. Background Art
[0002] Hydrogen is a renewable energy source with light weight, high energy density, water as its oxide, and is harmless to the environment. It is an ideal substitute for fossil energy. At present, hydrogen has extremely wide applications in social production and life such as aerospace materials, industrial reducing gases, hydrogen fuel cells, new energy power plant energy storage, biomedicine, etc. It is an energy carrier with very strong vitality. The main technical bottleneck restricting the development of the hydrogen economy is the storage of hydrogen. There are three main ways to store hydrogen: high-pressure gaseous hydrogen storage, low-temperature liquid hydrogen storage and solid hydrogen storage. High-pressure gaseous hydrogen storage and low-temperature liquid hydrogen storage have the advantages of easy dehydrogenation and wide working conditions, but they also have disadvantages such as easy hydrogen leakage, poor safety, and large evaporation losses, which cause a large amount of hydrogen to be wasted and increase the cost of hydrogen use. Solid-state hydrogen storage has the advantages of no evaporation loss, high safety, stable hydrogen storage performance, and suitability for long-term and long-distance storage. In recent years, it has received widespread attention from researchers.
[0003] Prior art 1, Chinese patent, application number 202210366610.8 discloses a membrane hydrogen storage material, preparation method and application. The membrane hydrogen storage material includes a film-forming fiber layer, and a solid hydrogen storage material is evenly distributed inside the film-forming fiber layer; the solid hydrogen storage material is combined with the film-forming fiber material to form a new type of membrane solid hydrogen storage material with flexibility, scalability, extensibility and high hydrogen storage density, convenient transportation and good safety performance. Although it can solve many problems of conventional solid hydrogen storage materials such as poor ductility, poor flexibility, and inconvenience for widespread application, and realize the controllability of hydrogen release. However, there are problems such as difficulty in material preparation and difficulty in the hydrogen storage and release process.
[0004] Prior art 2, Chinese patent, application number 202110191237.2 discloses a preparation method and solid hydrogen storage material of amino metal type solid hydrogen storage material. The amino metal type solid hydrogen storage material is prepared by mechanical ball milling with LiNH2 and MgH2 as the main raw materials; the preparation method includes a quality control process and an activation method during the preparation process, and the preparation process is accurately monitored by measuring the changes in the raw materials during the preparation of the amino metal compound hydrogen storage material to ensure the performance of the material obtained after subsequent activation, and the activation temperature is determined and the heating rate is regulated during the activation process. Although it effectively avoids the degradation of material performance caused by overheating of the material during activation and the safety hazards caused by overheating, kilogram-level high-purity amino metal hydrogen storage materials can be prepared in a single time, which is suitable for large-scale production and application of this type of hydrogen storage material. However, the material preparation is difficult, the material hydrogen storage test measurement is cumbersome, the hydrogen storage and release process kinetics are slow, and the hydrogen release is incomplete, which limits the application of solid-state hydrogen storage.
[0005] Prior art three, Chinese patent, application number 202210372866.X discloses an additive that can improve the hydrogen storage performance of lithium magnesium nitrogen hydride, and its preparation method and application; the preparation method comprises the following steps: (1) adding vanadium pentoxide to lithium carbonate solution, adding hydrazine hydrate after mixing, and then ultrasonically shaking to obtain a suspension; (2) transferring the suspension obtained in step (1) to a hydrothermal reactor, hydrothermally reacting at 100-120°C for 18-24h, and reacting the liquid obtained by the reaction with metavanadic acid After the ammonium is evenly mixed, the solution is evaporated to dryness, and the solid product is collected; (3) the solid product obtained in step (2) is heat treated at 500-550°C for 5-12 hours in a nitrogen or argon hydrogen mixed gas atmosphere to obtain the additive that can improve the hydrogen storage performance of lithium magnesium nitrogen hydride; the additive that can improve the hydrogen storage performance of lithium magnesium nitrogen hydride contains Li3VO4 and LiVO2, and the sum of the amounts of Li3VO4 and LiVO2 is 100%, and the amount of LiVO2 accounts for 35% to 50%. Although the hydrogen storage performance of lithium magnesium nitrogen hydride can be improved, the cost of solid-state hydrogen storage materials is increased, which prolongs the development cycle of materials.
[0006] At present, the existing technologies 1, 2 and 3 have the disadvantages of low hydrogen storage capacity, difficult hydrogen storage and release process, slow kinetics of hydrogen storage and release process, incomplete hydrogen release, etc., which limit the application of solid-state hydrogen storage; therefore, to develop high-performance solid-state hydrogen storage materials, it is necessary to improve the hydrogen adsorption performance of the materials while taking into account the kinetic characteristics of the materials in the hydrogen storage / release process; however, in the process of solid hydrogen storage material development, the difficulties in material preparation, the cumbersome material hydrogen storage test measurement, and the hydrogen storage performance of the prepared materials not meeting expectations not only increase the research and development cost of solid-state hydrogen storage materials, but also prolong the material development cycle; therefore, in the early stage of material development, accurate evaluation of the hydrogen adsorption characteristics and kinetic characteristics of the target material can greatly reduce the subsequent experimental costs and test cycles, and provide theoretical support and direction guidance for subsequent experimental measurements. Summary of the invention
[0007] The main purpose of the present invention is to provide a method and system for calculating and evaluating the hydrogen storage performance of solid hydrogen storage materials, so as to solve the problems of low hydrogen storage capacity, difficult hydrogen storage and release process, slow hydrogen storage and release process kinetics, and incomplete hydrogen release in the prior art.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material, comprising:
[0010] Using density functional theory (DFT) and molecular dynamics (MD), we build a microscopic model of the material to analyze and design the mechanical properties, electron distribution, thermal conductivity and thermal stability of the material itself.
[0011] Calculate the hydrogen adsorption performance of the newly designed hydrogen storage material by calculating the adsorption state, adsorption energy and hydrogen adsorption amount of the material at different pressures and temperatures of the hydrogen molecules on the hydrogen storage material;
[0012] Draw the hydrogen adsorption kinetic curve of solid-state hydrogen storage materials to calculate and evaluate the hydrogen storage kinetic performance of the materials.
[0013] As a further improvement of the present invention, the material microscopic model analysis process includes:
[0014] Use applied functional density theory to perform geometric optimization, determine the optimal lattice structure of the material, and use exchange-correlation functional to calculate the optimized structure of the material; obtain the electron density distribution of the optimized structure through calculation, and extract the electronic state, band structure and Fermi level information; analyze the conductive properties of the material, and determine its conductive and insulating properties through state density diagrams and band diagrams; use Bader charge analysis to evaluate charge transfer and localization phenomena, and obtain the chemical properties and reaction behaviors of the material; for the interaction potential between materials, select according to the characteristics of the material and the nature of the interaction;
[0015] Use the optimal geometric structure obtained by applying functional density theory as the initial configuration of molecular dynamics simulation; set temperature, pressure and time step parameters; run molecular dynamics simulation at different temperatures and pressures to obtain the thermal behavior, phase change process and mechanical response of the material; test the adsorption and diffusion behavior of gas molecules on the surface of the material to obtain dynamic information; apply external stress, generate stress-strain curves, and analyze the elastic modulus, yield strength and fracture behavior of the material; analyze the relative motion between atoms, extract the information of the displacement field, and obtain the changes in the mechanical properties of the material;
[0016] Use non-equilibrium molecular dynamics to analyze the thermal conductivity of materials at different temperatures; calculate lattice vibration and phonon heat conduction to evaluate the impact of thermal motion at the atomic level on macroscopic thermal conductivity; apply repeated thermal cycles in molecular dynamics to obtain the stability and deformation of materials in high-temperature environments; after the material reaches thermal equilibrium, evaluate its corresponding properties in the thermally excited state and identify potential phase transitions or degradation mechanisms.
[0017] As a further improvement of the present invention, the process of selecting the exchange-correlation functional to calculate the optimized structure of the material includes:
[0018] Extract the initial structure of the material using the database, including atomic positions and symmetries; set the geometry optimization parameters in the calculation software, and set the force and energy convergence criteria; start the calculation and run the geometry optimization;
[0019] Use the optimized crystal structure to perform self-consistent field calculations to obtain the electron density distribution. In the file output, view and analyze the electron density distribution diagram; select the k-point grid to calculate the energy band trend along a specific high-symmetry direction; generate the energy band diagram and state density diagram to analyze the filling state of each energy level; obtain the Fermi level position from the state density calculation and mark the Fermi level position in the energy band diagram;
[0020] Determine the properties of metals, semiconductors or insulators by the shape of the state density diagram; analyze the width of the band gap, calculate the conductivity and estimate the prediction model; use Bader charge analysis to calculate the charge value of each atom to ensure the correct distribution of local charges, present the charge distribution through visualization tools, and analyze which atoms or compounds receive or lose electrons; combine Bader results to analyze the degree of localization of electrons between different atoms and determine possible reaction active sites.
[0021] As a further improvement of the present invention, the process of calculating the hydrogen adsorption performance of the newly designed hydrogen storage material includes:
[0022] After obtaining a stable structure, a molecular dynamics simulation is performed, and the initial temperature and pressure are set; the MD simulation is run to obtain the dynamic stability and thermal stability data of the material, and the selected structure of the material at different temperatures is obtained;
[0023] Add hydrogen molecules to the optimized hydrogen storage material model, calculate different adsorption sites on the surface, vacancies or three-dimensional channels, calculate the energy of each site, identify the optimal adsorption site, evaluate the hydrogen adsorption energy at different sites, and select the adsorption site by comparing the adsorption energy at different sites;
[0024] Thermodynamic calculations are performed at different temperatures and pressures to evaluate the amount of hydrogen adsorbed in the material, and adsorption isotherms are used to estimate the adsorption amount under different conditions and quantify the hydrogen adsorption performance of the material.
[0025] As a further improvement of the present invention, the process of obtaining the selected structure of the material at different temperatures comprises:
[0026] Obtain the preliminary crystal structure of the hydrogen storage material and generate a three-dimensional model; perform geometric optimization on the initial structure, use the DFT method to calculate, optimize the coordinates of each atom, and obtain the lowest energy configuration; perform MD simulation for each target temperature;
[0027] Describe the interaction between atoms in the material and conduct thermal equilibrium under isobaric conditions at a set initial temperature; after reaching thermal equilibrium, continue to run the simulation to obtain the movement and changes of atoms inside the material; extract atomic coordinate data once and record the system configuration under the current temperature conditions;
[0028] The collected structural data are analyzed to calculate the atomic displacement, square displacement and average spacing properties of the material at different temperatures. The most stable and representative structures at different temperatures are screened out using the coordination number and distribution between atoms and the energy minimization criterion. The selected stable structures at different temperatures are summarized, visualized and a temperature spectrum is generated.
[0029] As a further improvement of the present invention, the process of identifying the optimal adsorption site includes:
[0030] Geometric description is performed on the surface and internal structure of hydrogen storage materials, and different possible hydrogen molecule adsorption sites are depicted using geometric features and spatial symmetry;
[0031] Synchronously introduce one or more hydrogen molecules into the model of the hydrogen storage material around the differently labeled adsorption sites; dynamically simulate the hydrogen molecules at the different adsorption sites; observe the movement of the hydrogen molecules under set initial conditions and record the interaction with the hydrogen storage material;
[0032] For each adsorption site, the potential energy relationship is used to calculate the interaction energy between the hydrogen molecule and the material; the relative stability of the hydrogen molecule at each adsorption site is obtained through an energy minimization program; the calculated adsorption energies are compared to identify the site with the lowest energy and mark it as the optimal adsorption site.
[0033] As a further improvement of the present invention, the process of quantifying the hydrogen adsorption performance of the material includes:
[0034] Using a gas adsorption isotherm measuring device, hydrogen is introduced into the pre-vacuum treated hydrogen storage material, and different hydrogen pressures are gradually applied; at each set pressure, the gas volume change, pressure change and temperature change during the adsorption process are monitored in real time through a range instrument;
[0035] The ideal gas state equation is used to calculate the amount of gas at a specific pressure, and the amount of hydrogen adsorbed is compared with the mass of the material to calculate the amount of hydrogen adsorbed per gram of material. The corresponding gas adsorption experiments are carried out under different temperature and pressure conditions. The adsorption isotherm model is used to fit the data and extract the thermodynamic parameters in the adsorption isotherm.
[0036] By calculating the adsorption isotherm and thermodynamic parameters, the maximum adsorption capacity of stored hydrogen and the transfer and release characteristics of the gas within the material are obtained; the adsorption efficiency under different conditions, including the saturated adsorption capacity, kinetic adsorption rate and desorption rate, is recorded and analyzed; the test results are compared with the adsorption performance of the hydrogen storage material.
[0037] As a further improvement of the present invention, the process of calculating and evaluating the hydrogen storage kinetic performance of the material includes:
[0038] The pressure sensor and flow meter are used to record the changes in pressure and flow of hydrogen at different time points in real time to form a dynamic monitoring data set; the data collected from the adsorption experiment are processed to calculate the hydrogen adsorption at different time points and record the changes in the amount of hydrogen at each time point;
[0039] Apply the ideal gas state equation, calculate the amount of substance corresponding to hydrogen adsorption based on the gas volume and pressure changes, and compare it with the material mass; use the acquired data to fit the hydrogen adsorption rate using a kinetic model to obtain the characteristics of the adsorption process;
[0040] Plot a curve of the relationship between the amount of hydrogen adsorbed on the hydrogen storage material and time on the coordinate scale to demonstrate the time dependence of hydrogen adsorption; extract key parameters from the plotted curve; calculate important kinetic parameters such as the hydrogen adsorption rate constant and diffusion coefficient to evaluate the hydrogen adsorption kinetic performance of the material.
[0041] As a further improvement of the present invention, the process of obtaining the characteristics of the adsorption process comprises:
[0042] The data of hydrogen adsorption and corresponding time are obtained to establish a structured data table, including time point, corresponding hydrogen pressure, flow rate, and hydrogen adsorption information; preliminary analysis is performed on the obtained data to draw a curve of hydrogen adsorption changing with time;
[0043] Select the fitting tool and use nonlinear least squares to minimize the error between the estimated model and the experimental data; input the experimental data and select the model equation;
[0044] Check the fit between the fitted curve and the actual data, output the key parameters of the fit, and calculate the goodness of fit. A value close to 1 indicates that the model predicts the adsorption behavior.
[0045] To achieve the above object, the present invention also provides the following technical solutions:
[0046] A solid hydrogen storage material hydrogen storage performance calculation and evaluation system, which is applied to the solid hydrogen storage material hydrogen storage performance calculation and evaluation method, the solid hydrogen storage material hydrogen storage performance calculation and evaluation system comprising:
[0047] Performance analysis module, which uses functional density theory and molecular dynamics to build a material microscopic model to analyze the mechanical properties, electronic distribution, thermal conductivity and thermal stability of the designed material itself;
[0048] Performance calculation module, used to calculate the hydrogen adsorption performance of the newly designed hydrogen storage material by calculating the adsorption state and adsorption energy of hydrogen molecules on the hydrogen storage material and the amount of hydrogen adsorbed by the material at different pressures and temperatures;
[0049] The performance evaluation module is used to draw the hydrogen adsorption kinetic curve of solid-state hydrogen storage materials to calculate and evaluate the hydrogen storage kinetic performance of the materials.
[0050] The construction and performance analysis of the material microscopic model of the present invention can construct a microscopic model of the material through DFT and MD methods, which allows the optimization of the material microstructure and the identification of the most promising material system; the mechanical properties, electronic distribution, thermal conductivity and thermal stability of the material can be deeply analyzed to provide the necessary preliminary data for understanding the basic physical and chemical properties of the material; through calculation and simulation, the behavior of the new material in the hydrogen storage process can be estimated, and its advantages and disadvantages can be identified, thereby providing guidance for subsequent experiments. Practical significance: It can effectively shorten the research and development cycle of new materials, avoid blind experiments through theoretical calculations, and improve research efficiency; an in-depth understanding of the physical and chemical properties of materials can provide an important reference for subsequent predictions and experiments on hydrogen adsorption performance, and enhance the scientific nature of the design. Hydrogen adsorption performance calculation, by calculating the adsorption state and adsorption energy of hydrogen molecules on hydrogen storage materials, can obtain the interaction strength between hydrogen molecules and materials. This provides a quantitative indicator for evaluating the hydrogen storage potential of materials; the calculation of hydrogen adsorption under different pressures and temperatures can reflect the performance of materials under actual hydrogen storage conditions, and provides data support for understanding the behavior of materials under common hydrogen storage conditions such as room temperature and high pressure; by evaluating the hydrogen adsorption of different materials, excellent hydrogen storage materials can be screened out, laying a solid foundation for subsequent experiments and practical applications. Practical significance: The detailed calculation and evaluation of hydrogen adsorption performance is helpful for material design according to specific application requirements and screening out the most promising candidate materials; by optimizing the hydrogen adsorption performance in materials, more efficient hydrogen storage can be ultimately achieved, promoting the practical application of renewable energy and hydrogen energy. Hydrogen adsorption kinetic performance evaluation, drawing hydrogen adsorption kinetic curves, can vividly display the hydrogen adsorption and release process of hydrogen storage materials, including speed, stability and dynamic characteristics; by analyzing the kinetic curves, the kinetic parameters in the hydrogen adsorption process, such as adsorption rate constant and diffusion coefficient, can be obtained, which is crucial for understanding the migration behavior of hydrogen inside the material; it realizes the overall evaluation of hydrogen storage performance at the macro level, ensuring that the screened materials not only have advantages in quantitative adsorption performance, but also perform well in adsorption and desorption kinetics. Practical significance: The evaluation of hydrogen adsorption kinetics provides the necessary dynamic characteristic analysis for the actual hydrogen storage application of the material, increasing the feasibility of the material in commercial applications. Through kinetic analysis, the bottlenecks that may exist in the operation of the material can be identified, promoting further design and optimization. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 A schematic flow chart of the steps of an embodiment of a method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material according to the present invention;
[0052] Figure 2 A schematic flow chart of the steps of a material microscopic model analysis process in one embodiment of a method for calculating and evaluating hydrogen storage performance of a solid hydrogen storage material of the present invention;
[0053] Figure 3 A schematic flow chart of the steps of calculating the hydrogen adsorption performance of a newly designed hydrogen storage material according to one embodiment of the method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material of the present invention;
[0054] Figure 4 A schematic flow chart of the steps of calculating and evaluating the hydrogen storage kinetics of a material in accordance with an embodiment of a method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material of the present invention;
[0055] Figure 5 A schematic diagram of functional modules of an embodiment of a system for calculating and evaluating hydrogen storage performance of solid hydrogen storage materials according to the present invention;
[0056] Figure 6 It is a structural schematic diagram of an embodiment of an electronic device of the present invention;
[0057] Figure 7 A schematic diagram of the structure of a storage medium according to an embodiment of the present invention;
[0058] Figure 8 Schematic diagram of the structure of the cellular model of the modified nitrided porous graphene of the present invention, (a), (b) and (c) are porous graphite, single and double Na-modified porous graphene respectively;
[0059] Fig. 9 Schematic diagram of the electronic energy band of sodium-modified nitrided porous graphene of the present invention, (a), (b) and (c) are the energy band structure diagrams of porous graphite, single and double Na-modified porous graphene respectively;
[0060] Fig.10 1 is a charge difference density diagram of the present invention, (a) and (b) are charge difference density diagrams of single and double Na-modified nitrided porous graphene, respectively;
[0061] Fig.11 The charge difference density diagram of hydrogen adsorbed on the surface of the material of the present invention, (a) and (b) are the result diagrams of single and double Na modified nitrided porous graphene respectively;
[0062] Fig.12 Schematic diagram of the electronic transmission characteristics of the material of the present invention, (a) is the conductivity, (b) is the power factor;
[0063] Fig.13 Schematic diagram of electronic thermal conductivity of the material of the present invention;
[0064] Fig.14 Schematic diagram of the phonon dispersion relation of the material of the present invention; (a), (b) and (c) are the result diagrams of porous graphite, single and double Na-modified porous graphene, respectively;
[0065] Fig.15 Schematic diagram of phonon relaxation time and group velocity of nitrided porous graphene of the present invention;
[0066] Fig.16 Schematic diagram of phonon thermal conductivity of the material of the present invention. DETAILED DESCRIPTION
[0067] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0068] The terms "first", "second" and "third" in the present invention are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Therefore, the features defined as "first", "second" and "third" can explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. All directional indications (such as up, down, left, right, front, back...) in the embodiments of the present invention are only used to explain the relative position relationship, movement, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication also changes accordingly. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally also includes steps or units that are not listed, or optionally also includes other steps or units inherent to these processes, methods, products or devices.
[0069] Reference to an "embodiment" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0070] like Figure 1 As shown, this embodiment provides an embodiment of a method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material. In this embodiment, the method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material specifically includes the following steps:
[0071] Step S1: Utilizing functional density theory and molecular dynamics methods, by constructing a material microscopic model, the mechanical properties, electron distribution, thermal conductivity, and thermal stability of the designed material itself are analyzed;
[0072] Step S2: calculating the hydrogen adsorption performance of the newly designed hydrogen storage material by calculating the adsorption state and adsorption energy of hydrogen molecules on the hydrogen storage material and the amount of hydrogen adsorbed by the material at different pressures and temperatures;
[0073] Step S3: Draw a hydrogen adsorption kinetic curve of the solid-state hydrogen storage material to calculate and evaluate the hydrogen storage kinetic performance of the material.
[0074] Preferably, in step S1 of this embodiment, the construction and performance analysis of the material microscopic model can construct a material microscopic model through DFT and MD methods, which allows the optimization of the material microstructure and the identification of the most promising material system; the mechanical properties, electronic distribution, thermal conductivity and thermal stability of the material can be deeply analyzed to provide the necessary preliminary data for understanding the basic physical and chemical properties of the material; through calculation and simulation, the behavior of the new material in the hydrogen storage process can be estimated, and its advantages and disadvantages can be identified, thereby providing guidance for subsequent experiments. Practical significance: It can effectively shorten the research and development cycle of new materials, avoid blind experiments through theoretical calculations, and improve research efficiency; an in-depth understanding of the physical and chemical properties of materials can provide an important reference for subsequent predictions and experiments on hydrogen adsorption performance, and enhance the scientific nature of the design. Step S2 Hydrogen adsorption performance calculation, by calculating the adsorption state and adsorption energy of hydrogen molecules on hydrogen storage materials, the interaction strength between hydrogen molecules and materials can be obtained. This provides a quantitative indicator for evaluating the hydrogen storage potential of materials; the calculation of hydrogen adsorption under different pressures and temperatures can reflect the performance of materials under actual hydrogen storage conditions, and provides data support for understanding the behavior of materials under common hydrogen storage conditions such as room temperature and high pressure; by evaluating the hydrogen adsorption of different materials, excellent hydrogen storage materials can be screened out, laying a solid foundation for subsequent experiments and practical applications. Practical significance: The detailed calculation and evaluation of hydrogen adsorption performance is helpful for material design according to specific application requirements and screening out the most promising candidate materials; by optimizing the hydrogen adsorption performance in materials, more efficient hydrogen storage can be ultimately achieved, promoting the practical application of renewable energy and hydrogen energy. Step S3 Hydrogen adsorption kinetic performance evaluation, drawing hydrogen adsorption kinetic curves, can vividly display the hydrogen adsorption and release process of hydrogen storage materials, including speed, stability and dynamic characteristics; by analyzing the kinetic curves, the kinetic parameters in the hydrogen adsorption process, such as adsorption rate constant and diffusion coefficient, can be obtained, which is crucial for understanding the migration behavior of hydrogen inside the material; the overall evaluation of hydrogen storage performance at the macro level is achieved, ensuring that the screened materials not only have advantages in quantitative adsorption performance, but also perform well in adsorption and desorption kinetics. Practical significance: The evaluation of hydrogen adsorption kinetics provides the necessary dynamic characteristic analysis for the actual hydrogen storage application of the material, increasing the feasibility of the material in commercial applications. Through kinetic analysis, the bottlenecks that may exist in the operation of the material can be identified, promoting further design and optimization.
[0075] In summary, this embodiment can comprehensively improve the research and development efficiency and hydrogen storage performance of solid hydrogen storage materials in theory and practical application through systematic analysis and evaluation of three steps. Each step provides important theoretical support and data basis when solving different technical challenges. It can not only accelerate the discovery and optimization of new materials and improve the efficiency of hydrogen storage, but also make positive contributions to the future utilization of hydrogen energy and the development of renewable energy.
[0076] This embodiment can perform comprehensive and accurate calculation and evaluation of the hydrogen storage performance of materials in the early stage of design and development of high-performance solid hydrogen storage materials, thereby simplifying the experimental exploration process, shortening the research and development cycle and cost of solid-state hydrogen storage materials, and providing theoretical support for experimental measurements. This embodiment can calculate and evaluate the hydrogen storage performance of the selected target material at the material selection stage in the early stage of solid-state hydrogen storage material development, and provide theoretical guidance for experimental measurements, thereby saving experimental costs and reducing experimental cycles; based on first-principles calculations, theoretical calculations can be performed on the thermal stability, mechanical properties, and electronic properties of solid-state hydrogen storage materials to clarify the characteristics and working characteristics of the material itself; based on first-principles calculations, the distribution characteristics of electrons adsorbed by hydrogen molecules on hydrogen storage materials can be calculated to clarify the adsorption state of hydrogen molecules on the material, thereby predicting the hydrogen adsorption capacity of the hydrogen storage material; based on first principles, the adsorption energy of hydrogen molecules on hydrogen storage materials can be calculated to determine the maximum number of hydrogen molecules that can be stably adsorbed by the hydrogen storage material, and calculate and evaluate the theoretical maximum hydrogen adsorption amount of the material; using molecular dynamics methods, the theoretical hydrogen adsorption amount of the material at different temperatures and pressures can be calculated; the hydrogen storage performance of solid-state hydrogen storage materials under different working conditions can be calculated and evaluated; using molecular dynamics methods, the hydrogen adsorption kinetic curves of solid-state hydrogen storage materials at different pressures can be calculated to calculate and evaluate the kinetic characteristics of the solid-state hydrogen storage material during the hydrogen storage / release process, thereby estimating the hydrogen storage / release time.
[0077] In this embodiment, the DFT method is used to theoretically calculate the hydrogen adsorption characteristics of the material, including the thermal stability of the material itself, the electronic distribution characteristics, the hydrogen adsorption characteristics at absolute zero, etc. The DFT method can calculate the electronic characteristics of the material, including the electronic band structure, electronic state density, electronic distribution, Bader charge, charge difference density, etc. through the VASP software package to determine the basic electronic characteristics of the research material and analyze the mechanism of the hydrogen storage process. The first principle is a calculation method based on quantum mechanics. It can calculate the structure, energy, magnetism, optics and other properties of the material from the most basic principles, with high accuracy and predictability. The first principle DFT is one of the most successful and popular methods in the field of solid physics and chemical calculation research. The theory solves the problem of the movement and interaction of atoms and molecules from the basic principle. The basic idea is to express all the physical quantities of the system as functionals of the electron density, that is, the energy, electron spin, charge density, etc. of the system. This function is usually called the exchange-correlation function, which contains two parts, exchange and correlation, which respectively describe the exchange between electrons and the interaction between electrons. The core idea of functional density theory is to transform the multi-body problem into a single-body problem and express the multi-body wave function as a function of electron density. According to the Hohenberg-Kohn theorem, the electron density uniquely determines all the physical properties of the system. Therefore, the electron density can be solved by minimizing the total energy functional. The total energy functional can be expressed as:
[0078]
[0079] Where, T s [ρ] represents the kinetic energy of the electron's degree of freedom, υ ext (r) represents the external potential field, ρ(r) represents the electron density, E XC [ρ] represents the exchange energy, which is caused by the interaction between electrons and the Pauli exclusion principle. The exchange correlation energy is the core of density functional theory, describing the interaction between electrons and the influence of the Pauli exclusion principle, and is the main difference between functional density theory and other computational chemistry methods.
[0080] The physical and chemical properties of solid-state hydrogen storage materials have an important influence on the hydrogen adsorption characteristics of the materials. They can be analyzed by calculating the band structure of the materials through the combination of VASP and VASPKIT software. The band structure is one of the tools in solid-state physics to qualitatively describe the characteristics of electron motion in crystals. It describes the energy that is forbidden or allowed to be carried by electrons, which is caused by the diffraction of quantum dynamics electron waves in periodic lattices. The band structure of the material determines many properties, especially its electronic properties. The central task of band calculation is to solve the single-electron Schrödinger equation in the periodic potential field of the crystal:
[0081]
[0082] Its solution should have the form of a Bloch function:
[0083] Ψ k (r) = e ikr u k (r)
[0084] u k (r) = u k (r+R n )
[0085] Therefore, when solving the problem, we should first find a reasonable approximate solution to represent u k (r) Or give a solvable approximate expression for the periodic potential field and solve the equation. From the energy band structure, we can determine whether the material is an insulator, semiconductor or metal, and then conduct further electronic structure analysis.
[0086] The energy band structure can be used to qualitatively understand the overall electronic properties of the material, while the charge distribution and differential charge distribution can be used to analyze the specific charge distribution in the material. Similarly, this result can be combined with VASP and VASPKIT software to calculate the electronic state density, electron distribution, Bader charge and charge differential density of the material for analysis. The distribution of electrons in space is a cloud of electrons. The purpose of charge analysis is to use a concise method to describe this chaotic electron cloud distribution and the number of charges around the atoms in the system. Charge distribution is widely used in studies that need to describe the charge state of the system. Charge density analysis can be used to analyze the bonding information between atoms. When charge density analysis cannot display bonding information, differential charge density can be considered. The differential charge density is the difference between the charge density after atomic interaction and the atomic charge density of the corresponding point, which helps to understand the adsorption state between hydrogen molecules and solid-state hydrogen storage materials. Through differential charge density analysis, properties such as charge movement and bonding polarization direction in the bonding and bonding electron coupling process can be clearly obtained. The differential charge density calculation formula is:
[0087] Δρ=ρ AB -ρ A -ρ B
[0088] where ρ AB Represents the charge density of the structure after the combination of materials A and B, ρ A and ρ B are the structural charge densities of materials A and B before combination. Subtracting them, we can get the charge density change after materials A and B form material AB, and then analyze the properties such as charge transfer. The characteristics of the interaction between the material and the hydrogen molecules can be preliminarily determined from the charge transfer characteristics.
[0089] Thermal conductivity has a great influence on the hydrogen storage kinetics of solid-state hydrogen storage materials. Materials with high thermal conductivity have a faster response speed in the temperature control of the hydrogen storage and desorption process, so the hydrogen storage kinetics are better. The thermal conductivity of the material includes electronic thermal conductivity and phonon thermal conductivity. The DFT method can be used in conjunction with the VASP, VASPKIT, and BoltzTraP2 software packages to calculate the effective mass of the carriers, elastic constants, electron relaxation time, electronic thermal conductivity, power factor, electronic thermal conductivity, etc. of the material to study the mechanical properties and electronic thermal conductivity of the material. Its hot carriers are electrons and phonons. In the material, free electrons with high temperatures will move faster, diffuse rapidly around, and exchange energy with cold electrons (electrons with low temperatures) through collisions, and transfer heat. The electronic thermal conductivity of the material (κ e ) can be calculated using the Wiedemann-Franz law:
[0090] κ e =LσT
[0091] Where T is temperature, σ is conductivity, and L is the Lorentz constant. The calculation formula for the Lorentz constant is:
[0092]
[0093] where k B is the Boltzmann constant; e is the electron charge; r is the scattering radius of various scattering mechanisms; η is the Fermi energy; F n (η) is the nth order Fermi integral. Boltztrap software can be used to obtain the σ / τ and S of the material. Then the electron relaxation time (τ) is calculated based on the deformation potential theory, and the conductivity is obtained. The electron relaxation time can be calculated according to the following formula:
[0094]
[0095] where k B , m* and E1 are the Boltzmann constant, Planck constant, electron effective mass and phase transition potential energy respectively; C is the elastic constant. The elastic constant describes the response stiffness of the crystal to the applied strain, and the stress and strain of the system satisfy Hooke's law. In general, the elastic constant is represented by a matrix, which can be used as a basis for determining the stability of the material. According to the Born stability criterion, if a material is stable, the following conditions must be met: the matrix C is positive definite; all eigenvalues of the matrix C are positive; all ordered principal minors of the matrix C are positive; any minor of the matrix C is positive.
[0096] In general, phonons make a major contribution to the heat transfer process of solid-state hydrogen storage materials. Through the DFT method, using VASP in combination with Alamode software, the phonon properties of the material, including phonon dispersion relations, phonon relaxation time, phonon group velocity, lattice thermal conductivity, etc., can be calculated to study the thermal stability of the material and the phonon thermal conductivity characteristics. The solid lattice has a periodic structure, and atoms or ions vibrate around the equilibrium position to form phonons. Phonons are carriers of the thermal conductivity of the material lattice. According to the ideal gas model assumption, the lattice thermal conductivity of the material is:
[0097]
[0098] Among them C V is the constant volume heat capacity, v g is the phonon group velocity, l is the mean free path, and τ is the phonon relaxation time. V It is the characteristic parameter of the material itself. When the material structure remains unchanged, it only changes with the temperature. g It can be obtained based on the slope of the phonon branch in the phonon dispersion relation. In addition, the thermal stability of the material can also be determined based on the phonon dispersion relation. If the phonon dispersion relation of the material shows an imaginary frequency (phonons with negative frequency) at a certain temperature, it means that the material is structurally unstable at this temperature. According to Matheson's rule, if there are multiple scattering mechanisms in the material, the phonon relaxation time can be written as follows:
[0099]
[0100] where τ U , τ B、 τ Str、 τ Res、 τ EP They are relaxation time components caused by U scattering process, point defect scattering, grain boundary scattering, dislocation scattering, non-magnetic phonon resonance scattering and electroacoustic scattering. Through calculation, the thermal conductivity of solid hydrogen storage materials has been fully discussed. The above material properties are all calculated by first principles. Since the first principles can only calculate the relevant properties of the material at absolute zero, the hydrogen adsorption characteristics and kinetic characteristics of the material at working temperature cannot be evaluated by the first principles.
[0101] In response to the above problems, the MD method was used, and the LAMMPS software was used to select a suitable force field to calculate and evaluate the hydrogen adsorption and kinetic properties of the material at different temperatures and pressures. Molecular dynamics is a computational simulation method that studies the microscopic and macroscopic properties of a system by simulating the motion trajectories of atoms and molecules in the system. It is an important means to study molecular systems. Based on Newtonian classical mechanics, as long as the interactions between atoms and molecules in a molecular system are given, the motion trajectories of molecules or atoms can be solved, and then certain statistical methods can be used to calculate the mechanical, thermodynamic, and kinetic properties of the system. In molecular dynamics, the intermolecular potential U(r) is usually used to represent the intermolecular interaction, and r is the intermolecular distance. Therefore, the intermolecular interaction potential determines the structural properties and physicochemical properties of the substance. Taking the most common intermolecular potential Lennard-Jones potential as an example, its mathematical expression is:
[0102]
[0103] Among them, r = σ is the zero potential energy position of the system potential energy, and ε is the potential well depth. For different systems, appropriate potential functions should be selected to improve the accuracy of calculations.
[0104] Molecular dynamics is a good supplement to the first principles method. Since the first principles can only calculate the electronic properties of the system at absolute zero, and the computing resources are large, it can only calculate systems with a small number of atoms. Therefore, the first principles are only suitable for the mechanism analysis of electronic and energy properties. Molecular dynamics can calculate larger systems, analyze the energy and kinetic properties at different temperatures and pressures, but it cannot analyze the electronic properties of the system. Therefore, combining the first principles with molecular dynamics can take the advantages of both methods and complement each other, so as to conduct more comprehensive and accurate calculation and evaluation of hydrogen storage material performance.
[0105] Furthermore, if Figure 2 As shown, the material microscopic model analysis process in step S1 specifically includes the following steps:
[0106] Step S11: Use the applied functional density theory to perform geometry optimization, determine the optimal lattice structure of the material, and use the exchange-correlation functional to calculate the optimized structure of the material; obtain the electron density distribution of the optimized structure through calculation, and extract information such as the electronic state, band structure, and Fermi level;
[0107] Analyze the conductive properties of materials, and determine their conductive and insulating properties through density of states and energy band diagrams; use Bader charge analysis or other methods to evaluate charge transfer and localization phenomena, and obtain the chemical properties and reaction behaviors of materials; for the interaction potential between materials, use Lennard-Jones potential, EAM potential (embedded atom model), Tersoff potential, etc., according to the characteristics of the materials and the nature of the interaction;
[0108] Step S12: using the optimal geometry obtained by applying functional density theory as the initial configuration for molecular dynamics simulation;
[0109] Set parameters such as temperature, pressure and time step; run molecular dynamics simulation at different temperatures and pressures to obtain the thermal behavior, phase change process and mechanical response of the material; test the adsorption and diffusion behavior of gas (such as hydrogen, oxygen, etc.) molecules on the material surface to obtain dynamic information;
[0110] Apply external stress, generate stress-strain curve, analyze the elastic modulus, yield strength and fracture behavior of the material; analyze the relative motion between atoms, extract the information of displacement field, and obtain the change of mechanical properties of the material;
[0111] Step S13: Use non-equilibrium molecular dynamics to analyze the thermal conductivity of the material at different temperatures; calculate lattice vibration and phonon heat conduction to evaluate the effect of thermal motion at the atomic level on macroscopic thermal conductivity; apply repeated thermal cycles in molecular dynamics to obtain the stability and deformation of the material in a high temperature environment;
[0112] After the material reaches thermal equilibrium, the corresponding properties in its thermally excited state are evaluated to identify potential phase transitions or degradation mechanisms.
[0113] Preferably, in step S11 of this embodiment, DFT geometry optimization and electronic structure analysis are used to optimize the geometry of the material through DFT to ensure that the atomic arrangement reaches the lowest energy state and obtain a stable lattice structure; the electron density distribution of the material is calculated, and the electronic state, band structure and Fermi level are analyzed based on this to determine the conductive properties and insulating properties of the material; the charge localization and transfer phenomena are evaluated using methods such as Bader charge analysis to obtain the chemical properties and reaction behaviors of the material; a suitable intermolecular potential (such as Lennard-Jones potential, EAM potential, etc.) is selected according to the properties of the material to lay the foundation for the subsequent molecular dynamics simulation. The significance achieved: providing an accurate initial structure for subsequent molecular dynamics simulations to ensure the reliability of the calculation results; helping to understand the chemical behavior, reactivity and potential applications of the material through in-depth analysis of the electronic structure and charge distribution; providing an important theoretical basis for the improvement of materials and the design of new materials by identifying the electronic properties of the material. Step S12: Molecular dynamics simulation setup and analysis. Use the crystal structure obtained through DFT optimization as the initial configuration of the molecular dynamics simulation. Run molecular dynamics simulations under different temperature and pressure conditions to observe the thermal behavior, phase change process and mechanical response of the material. Test the adsorption and diffusion behavior of gas molecules (such as hydrogen, oxygen, etc.) on the surface of the material to obtain its dynamic characteristics. Apply external stress to generate stress-strain curves to analyze the elastic modulus, yield strength and fracture behavior of the material. Significance achieved: The dynamic data obtained through MD simulation strengthens the understanding of the behavior of the material under actual application conditions. The generation and analysis of stress-strain curves can help identify the mechanical limits of the material and guide material optimization and application design. Understanding the interaction between the material and the gas molecules is helpful for application development in the fields of catalysis and hydrogen storage. Step S13 thermal conductivity and thermal stability analysis, using non-equilibrium molecular dynamics method, analyze the thermal conductivity of materials at different temperatures to obtain the thermal conductivity of materials; calculate the lattice vibration mode in the material, and evaluate the influence of thermal motion at the atomic level on the macroscopic thermal conductivity through the phonon scattering mechanism; apply thermal cycle conditions to observe the behavior of the material in a high temperature environment, evaluate its thermal stability and potential structural changes; evaluate the thermally excited state of the material after it reaches thermal equilibrium, and identify possible phase changes or degradation mechanisms. Significance achieved: Through thermal conductivity and thermal stability analysis, the reliability and performance of materials in high temperature applications can be evaluated; understanding the thermal conductivity characteristics of materials can provide guidance for the design of thermal management materials, such as for the development of thermal barrier materials or thermally conductive composite materials; by identifying phase changes and degradation mechanisms at high temperatures, it helps to ensure the safety and stability of materials in various environments.
[0114] In summary, in the process of material micro-model analysis in this embodiment, each step from DFT optimization, MD simulation to thermal performance analysis complements each other to form a complete research framework. Each step not only has an independent technical effect, but also contributes to the in-depth understanding and optimization of material properties, providing strong support for the combination of material science theory and material engineering practice. It is helpful to promote the development and application of new materials and meet the needs of future science, technology and industry.
[0115] Furthermore, the process of selecting the exchange-correlation functional to calculate the optimized structure of the material in step S11 specifically includes the following steps:
[0116] Step S111: extracting the initial structure of the material using the database, including atomic positions, symmetry, etc.; setting geometry optimization parameters in the calculation software, setting force and energy convergence criteria; starting the calculation, and running the geometry optimization;
[0117] Step S112: Use the optimized crystal structure to perform self-consistent field calculation to obtain the electron density distribution. In the file output, view and analyze the electron density distribution diagram; select the k-point grid to calculate the energy band trend along a specific high-symmetry direction; generate the energy band diagram and state density diagram, and analyze the filling state of each energy level; obtain the Fermi level position from the state density calculation, and mark the position of the Fermi level in the energy band diagram;
[0118] Step S113: Determine the properties of metals, semiconductors or insulators by the shape of the state density diagram; analyze the band gap width, calculate the conductivity and estimate the prediction model; use Bader charge analysis to calculate the charge value of each atom to ensure the correct distribution of local charges, present the charge distribution through visualization tools, and analyze which atoms or compounds receive or lose electrons; combine the Bader results to analyze the degree of localization of electrons between different atoms and determine possible reaction active sites.
[0119] Preferably, in step S111 of this embodiment, the geometry optimization is to extract the crystal structure of the material from the material database (such as Materials Project, AFLOW, ICSD, etc.), including the atomic position, atomic type, symmetry information and lattice parameters; to ensure the validity and reliability of the calculation results; to set the algorithm, convergence standard (energy and force) and k-point grid related to geometry optimization in the calculation software, the force convergence standard ensures that no numerical oscillation will be caused during the optimization process, and the energy convergence standard ensures the accuracy of the results; after starting the calculation, the software iteratively adjusts the atomic position according to the selected algorithm, reduces the system energy, and finally obtains a stable crystal structure. The significance achieved: With the optimized crystal structure as the benchmark for subsequent calculations and simulations, ensure that any further calculation results are based on a stable and reliable system state; through geometry optimization, ensure that the geometric structure of the material accurately reflects the actual situation in its lowest energy state, and lay the foundation for understanding the physical and chemical properties of the material. Step S112: Calculate the electronic structure. Use the optimized crystal structure to perform self-consistent field calculations to obtain the electron density distribution of the material. This allows visualization of the distribution of electrons in the material, which helps understand the effects of different types of atoms on the electronic state. Select an appropriate k-point grid, then calculate the band structure and generate the corresponding band diagram and state density diagram (DOS). The diagram clearly shows the filling of the electronic state, indicating the conductivity or insulation of the material. The Fermi level position is obtained through the state density diagram and marked on the band diagram. The determination of the Fermi level is crucial for judging the conductive properties of the material and understanding the behavior of the electronic state. Significance achieved: Provide a detailed theoretical basis for the electrical properties of the material, be able to predict the conductivity of the material under different conditions, and further support the design and application of new materials. The analysis of the band diagram and state density diagram helps researchers determine the applicability of materials in a wide range of application scenarios, such as new energy, electronic devices, and other fields. Step S113 Conductive properties and charge analysis: By analyzing the density of states diagram and the band gap width, the conductive properties of the material (such as metal, semiconductor or insulator) are determined, and its performance in practical applications is predicted; through Bader charge analysis, the charge value of each atom is calculated, and the charge distribution is presented using visualization tools to provide information for understanding the charge transfer and localization phenomena between atoms, especially for identifying possible reactive sites. Significance achieved: Through charge analysis, researchers can confirm the possible active sites of materials in processes such as catalysis and sensing, and provide guidance for subsequent experimental research; by understanding the localization and transfer phenomena of electrons, more forward-looking and targeted material improvement plans can be designed to meet specific functional and performance requirements.
[0120] In summary, the entire process of this embodiment, from geometry optimization to electronic structure calculation, and then to conductive properties and charge analysis, forms a systematic research framework. This systematic approach can greatly improve the efficiency and accuracy of material development and provide necessary support for the research and application of new materials.
[0121] Furthermore, if Figure 3 As shown, the process of calculating the hydrogen adsorption performance of the newly designed hydrogen storage material in step S2 specifically includes the following steps:
[0122] Step S21: After obtaining a stable structure, a molecular dynamics simulation is performed, and the initial temperature and pressure are set; the MD simulation is run to obtain the kinetic stability and thermal stability data of the material, and the selected structure of the material at different temperatures is obtained;
[0123] Step S22: adding hydrogen molecules to the optimized hydrogen storage material model, calculating different adsorption sites such as surface, vacancies or three-dimensional channels, performing energy calculations on each site, identifying the optimal adsorption site, evaluating the hydrogen adsorption energy at different sites, and selecting the adsorption site by comparing the adsorption energies at different sites;
[0124] Step S23: Perform thermodynamic calculations at different temperatures and pressures to evaluate the amount of hydrogen adsorbed in the material, use adsorption isotherms to estimate the amount of adsorption under different conditions, and quantify the hydrogen adsorption performance of the material.
[0125] Preferably, step S21 of this embodiment systematically analyzes the atomic motion and structural changes of the material under different initial temperature and pressure conditions through MD simulation, which helps to identify the stable state of the material under dynamic conditions; by observing and simulating the reaction of the material over time, the thermal stability and thermal properties of the material are evaluated, such as whether the material will undergo phase change, dissociation or lose structural integrity under high temperature conditions; at different temperatures, a variety of structural state information of the material is collected, including lattice constants, atomic positions, relative energy, etc. These data are crucial for subsequent adsorption performance analysis. Significance: By obtaining a dynamically stable structure, it can provide a basis for material optimization and ensure that subsequent adsorption performance analysis is based on a stable foundation; the thermal stability of the material is a key factor in determining whether it can be used for a long time in actual hydrogen storage applications, and improves the understanding of the application prospects of the material. Step S22 calculates the energy of hydrogen molecule adsorption sites, by adding hydrogen molecules to the optimized hydrogen storage material, and performing energy calculations on different adsorption sites (such as surfaces, vacancies or three-dimensional channels), which helps to evaluate the adsorption tendency and ability of hydrogen; identifies the site with the lowest adsorption energy, provides the area most conducive to hydrogen adsorption, and provides a basis for achieving efficient hydrogen storage. Significance: Understanding the adsorption capacity of hydrogen molecules at different locations can guide how to optimize the microstructure of hydrogen storage materials, thereby increasing hydrogen storage capacity; by selecting the optimal adsorption site, increasing the amount of hydrogen adsorbed, and improving the overall hydrogen adsorption performance of hydrogen storage materials, it is the key to achieve efficient hydrogen storage. Step S23 Thermodynamic calculation and adsorption isotherm analysis; under different temperature and pressure conditions, through thermodynamic calculations, the amount of hydrogen adsorbed in the material is systematically evaluated, providing quantitative data for understanding how the material stores hydrogen in practical applications; using adsorption isotherms (such as Langmuir or BET models), by fitting different data points to quantify the amount of hydrogen adsorption and adsorption characteristics, providing standards for hydrogen storage behavior under different conditions. Significance: Based on the quantified adsorption performance, it can be compared with other known materials to evaluate the advantages and disadvantages of the newly designed materials relative to the existing technology; through quantitative analysis, the design and optimization of hydrogen adsorption materials can be further improved in experiments and engineering applications to better meet specific hydrogen storage needs.
[0126] In summary, this embodiment uses the above steps to calculate the hydrogen adsorption performance of the newly designed hydrogen storage material, which can systematically evaluate the kinetic and thermodynamic properties of the material, which not only provides guidance for the optimization and application of the material, but also plays an important role in promoting the application of clean energy technology (such as hydrogen energy) in practice. The results of each stage complement each other and provide a solid foundation for the development and innovation of materials science.
[0127] Furthermore, the process of obtaining the selected structure of the material at different temperatures in step S21 specifically includes the following steps:
[0128] Step S211: obtaining a preliminary crystal structure of the hydrogen storage material and generating a three-dimensional model; performing geometric optimization on the initial structure, using the DFT method to perform calculations, optimizing the coordinates of each atom, and obtaining the lowest energy configuration; performing MD simulation for each target temperature;
[0129] Step S212: Describe the interaction between atoms of the material, and perform thermal equilibrium under isobaric conditions at a set initial temperature; after reaching thermal equilibrium, continue to run the simulation to obtain the movement and changes of atoms inside the material; extract atomic coordinate data once every certain period of time (for example, 0.1 nanoseconds) to record the system configuration under the current temperature conditions;
[0130] Step S213: Analyze the collected structural data, calculate the atomic displacement, square displacement and average spacing and other properties of the material at different temperatures; use the coordination number and distribution between atoms and energy minimization and other criteria to screen out the most stable and representative structures at different temperatures; summarize the selected stable structures at different temperatures, visualize and generate a temperature spectrum.
[0131] Preferably, in step S211 of this embodiment, the preliminary model construction and geometry optimization are performed by obtaining the preliminary crystal structure of the hydrogen storage material from the literature or database and generating a three-dimensional model to lay the foundation for subsequent calculations; the initial structure is geometrically optimized using methods such as density functional theory (DFT), which can not only minimize the total energy of the material, but also identify and adjust the undesirable atomic positions; through optimization, the coordinates of each atom are ensured to obtain the best configuration so that the material is thermodynamically stable. Significance: Geometric optimization ensures that the atoms are arranged reasonably, and the material has better stability and reliability under operating conditions, providing a credible starting structure for molecular dynamics simulations; the optimized structure has a key influence on the results of subsequent dynamic and thermodynamic calculations, and is directly related to the accurate evaluation of the hydrogen adsorption performance of the material. Step S212: Molecular dynamics simulation and thermal equilibrium. In molecular dynamics simulation, a reasonable potential energy function or force field can accurately simulate the interaction between atomic groups, thereby better showing the dynamic properties of the material. By setting the initial temperature for thermal equilibrium, the structural changes of the material during the heating process can be observed to ensure that the temperature and pressure of the system reach a stable state. By regularly extracting atomic coordinate data during the simulation run, the dynamic behavior and atomic distribution of the material at a specific temperature can be collected. Significance: Dynamic simulation after thermal equilibrium helps to understand the motion characteristics of the material under different temperature conditions, predict how the material responds to external temperature and pressure changes, and thus make a reasonable assessment of its application prospects. Subsequent analysis of the collected trajectory data is the basis for evaluating material performance. Reliable energy calculations and property assessments can only be performed with the support of a sufficient database. Step S213 structural data analysis and stable structure screening, analyze the collected structural data, calculate atomic displacement, square displacement, average atomic distance, coordination number, etc. By comparing these physical properties, the stability and applicability of the material at different temperatures can be evaluated; the most stable and representative structures exhibited at different temperatures are identified using the standards of atomic coordination number and energy minimization to ensure that the obtained model can truly reflect the state of the material in practical applications; the generated temperature spectrum visualizes the structural changes and characterization of the material when affected by temperature, making the research results more intuitive and helpful for a better understanding of the material properties. Significance: By quantitatively analyzing the characteristics of the selected structure at different temperatures, it is possible to provide empirical support for the analysis of hydrogen adsorption performance, which is of great significance to scientific research and engineering applications; the selected stable structure not only provides a basis for further optimization of hydrogen storage materials, but also provides direction for the design and synthesis of new materials, promoting the development of hydrogen storage technology.
[0132] In summary, through the above steps, the present embodiment systematically obtains the selected structure of hydrogen storage materials at different temperatures throughout the entire process, ensuring that the final structure can meet diverse needs in terms of function, performance and practicality. This helps to deeply understand the behavior of materials and provides a solid foundation for future theoretical and applied research in the field of hydrogen storage.
[0133] Furthermore, the process of identifying the optimal adsorption site in step S22 specifically includes the following steps:
[0134] Step S221: geometrically describe the surface and internal structure of the hydrogen storage material, and use geometric features and spatial symmetry to depict different possible hydrogen molecule adsorption sites;
[0135] Among them, the delineated sites should include: above the surface atoms ("top site"), in the middle ("bridge site"), and vacancies inside the pores, etc.;
[0136] Step S222: Synchronously introduce one or more hydrogen molecules into the model of the hydrogen storage material around the differently labeled adsorption sites; dynamically simulate the hydrogen molecules at the different adsorption sites; observe the movement of the hydrogen molecules under the set initial conditions, and record the interaction with the hydrogen storage material;
[0137] Step S223: For each adsorption site, the interaction energy between the hydrogen molecule and the material is calculated using the potential energy relationship; the relative stability of the hydrogen molecule at each adsorption site is obtained through an energy minimization program; the calculated adsorption energies are compared to identify the site with the lowest energy and mark it as the optimal adsorption site.
[0138] Preferably, in step S221 of this embodiment, the geometric description and adsorption site delineation can identify possible hydrogen molecule adsorption sites by analyzing the geometric structure and spatial symmetry of the hydrogen storage material; the selection of sites is mainly based on the arrangement of atoms on the surface of the material and their relationship with adjacent atoms; different types of adsorption sites (such as top sites, bridge sites and vacancies in the pores) are delineated according to the structural characteristics of the hydrogen storage material, setting the foundation for subsequent computational simulation and analysis. Significance: It lays a solid foundation for subsequent adsorption simulation and energy calculation, ensuring that all possible hydrogen molecule adsorption sites are covered to the maximum extent and improving the comprehensive performance of the model; by accurately delineating the adsorption sites, experiments can be designed more effectively, unnecessary calculation and simulation time can be reduced, and research efficiency can be improved. Step S222: Dynamic simulation of hydrogen molecules, synchronously introduce hydrogen molecules into the computational model of hydrogen storage materials, and study the dynamic behavior of hydrogen molecules at different adsorption sites through MD simulation; under the set initial conditions (such as temperature and pressure), observe the motion trajectory of hydrogen molecules, and collect relevant data on the interaction between hydrogen molecules and materials. Significance: Through dynamic simulation, we can better understand the movement of hydrogen molecules in hydrogen storage materials and their impact on material structure, and enhance our understanding of the hydrogen adsorption behavior of materials; provide necessary dynamic information for subsequent energy calculations, make the calculation results more realistic, and improve the credibility of simulation results. Step S223 Interaction energy calculation and optimal site identification, using force field and potential energy relationship, calculate the interaction energy (adsorption energy) of hydrogen molecules at each adsorption site, and provide quantitative data for evaluating adsorption capacity; evaluate the relative stability of hydrogen molecules at each adsorption site through energy minimization program to ensure that the selected optimal site has the lowest energy. Significance: Comparing the energy of each adsorption site can clarify their respective adsorption capacities, identify the adsorption site with the lowest energy, and mark it as the optimal adsorption site, which is the key to optimizing the performance of hydrogen storage materials; identifying the optimal adsorption site not only provides important data support for the application of hydrogen storage materials, but also provides a clear direction for the design and optimization of future materials.
[0139] In summary, the process of identifying the optimal hydrogen adsorption site in this embodiment has gradually improved the accuracy and effectiveness of hydrogen adsorption performance research through refined steps. It provides a scientific basis for understanding and optimizing the hydrogen adsorption capacity of hydrogen storage materials. The research results not only enrich the understanding of hydrogen storage materials in theory, but also promote future application development in reality.
[0140] Furthermore, the process of quantifying the hydrogen adsorption performance of the material in step S23 specifically includes the following steps:
[0141] Step S231: using a gas adsorption isotherm measuring device, introducing hydrogen into the pre-vacuum treated hydrogen storage material, and gradually applying different hydrogen pressures; at each set pressure, using a range instrument to monitor in real time the gas volume change, pressure change and temperature change during the adsorption process;
[0142] Step S232: Calculate the amount of gas at a specific pressure using the ideal gas state equation, compare the amount of adsorbed hydrogen with the mass of the material, and calculate the amount of hydrogen adsorbed per gram of the material; perform corresponding gas adsorption experiments under different temperature and pressure conditions; apply the adsorption isotherm model to perform data fitting and extract thermodynamic parameters in the adsorption isotherm;
[0143] Step S233: Obtain the maximum adsorption capacity of stored hydrogen and the transfer and release characteristics of the gas within the material by calculating the adsorption isotherm and thermodynamic parameters; record and analyze the adsorption performance under different conditions, including the saturated adsorption capacity, kinetic adsorption rate and desorption rate; compare the test results with the adsorption performance of the hydrogen storage material.
[0144] Preferably, in the step S231 of this embodiment, the gas adsorption experiment is carried out by using a gas adsorption isotherm measuring device to introduce hydrogen into the vacuum-treated hydrogen storage material, and gradually apply different hydrogen pressures. In this process, the gas volume, pressure and temperature changes during the adsorption process are monitored in real time by a range instrument to ensure the accuracy and stability of data acquisition; through real-time monitoring, a dynamic adsorption behavior model of the gas in the material can be generated to provide original data support for subsequent data analysis. Significance: Ensure that the experiment is carried out under controlled conditions so that oxidation, humidity or other external factors will not interfere with the hydrogen adsorption process, thereby improving the credibility of the results; record the corresponding gas changes to provide a basis for subsequent quantitative analysis and ensure that there is sufficient data support when evaluating material properties. Step S232 Calculation of hydrogen adsorption amount, calculate the amount of substance change of the gas under a specific pressure through the ideal gas state equation (PV=nRT), thereby obtaining the amount of adsorbed hydrogen; compare the amount of adsorbed hydrogen with the mass of the hydrogen storage material, and calculate the amount of hydrogen adsorption per gram of material, including the corresponding data at different temperatures and pressures. Significance: Quantifying the hydrogen adsorption capacity enables the performance of the material to be described by quantifiable parameters (such as wt% or mol / kg), thereby providing a basis for evaluating its practical application potential; through data fitting and the application of the adsorption isotherm model, thermodynamic parameters (such as adsorption energy, specific surface area, etc.) can be extracted to provide an in-depth basis for understanding the internal mechanism of the material. Step S233 Characteristic analysis and result comparison: By calculating the adsorption isotherm and thermodynamic parameters, the maximum hydrogen adsorption amount is obtained, and the gas transfer and release characteristics inside the material are analyzed, including saturated adsorption amount, adsorption and desorption rate, etc.; the obtained test results are compared with the performance of hydrogen storage materials in existing literature to determine the advantages or disadvantages of the studied material in terms of hydrogen adsorption capacity. Significance: The analysis of the maximum adsorption amount and gas transfer characteristics provides a scientific basis for in-depth understanding of the behavior of the material in hydrogen storage, and helps to explain the internal mechanism of the material performance; by comparing with other hydrogen storage materials, the feasibility of the material in practical applications can be quickly identified, promoting more effective material screening and optimization, and helping to promote the development of hydrogen energy technology.
[0145] In summary, each step of this embodiment plays an indispensable role in quantifying the hydrogen adsorption performance of hydrogen storage materials. Through systematic experiments, data analysis and performance comparison, not only the accuracy and reliability of the results are ensured, but also a clear direction is provided for the optimization of hydrogen storage materials. It enhances the in-depth understanding of material properties, so that future research and application development have stronger scientific basis and technical reference.
[0146] Furthermore, if Figure 4 As shown, the process of calculating and evaluating the hydrogen storage kinetics performance of the material in step S3 specifically includes the following steps:
[0147] Step S31: Record the pressure and flow changes of hydrogen at different time points in real time through the pressure sensor and flow meter to form a dynamic monitoring data set; process the data collected from the adsorption experiment, calculate the hydrogen adsorption at different time points, and record the change of hydrogen amount at each time node;
[0148] Step S32: applying the ideal gas state equation, calculating the amount of substance corresponding to hydrogen adsorption according to the gas volume and pressure changes, and comparing it with the material mass; using the acquired data, applying a kinetic model (such as Langmuir or BET model) to fit the hydrogen adsorption rate to obtain the characteristics of the adsorption process;
[0149] Step S33: Draw a curve of the relationship between the amount of hydrogen adsorbed on the hydrogen storage material (y-axis) and time (x-axis) on the coordinate scale to show the time dependence of hydrogen adsorption; extract key parameters from the drawn curve, such as the initial adsorption rate, equilibrium adsorption amount and dynamic equilibrium time; calculate important kinetic parameters such as the adsorption rate constant and diffusion coefficient of hydrogen, and evaluate the hydrogen adsorption kinetic performance of the material.
[0150] Preferably, in step S31 of this embodiment, real-time data recording and processing is performed, and the pressure and flow changes of hydrogen at different time points are recorded in real time by pressure sensors and flow meters to form a comprehensive dynamic monitoring data set, which provides basic data; based on real-time data, the amount of hydrogen adsorption at each time node is calculated to establish a direct connection between the hydrogen adsorption process and time. Significance: Real-time data extraction provides a complete view of the hydrogen adsorption process, ensuring the reliability and accuracy of the data; the cornerstone of further analysis and model fitting; understanding the different stages of the adsorption process of hydrogen in the material makes the subsequent analysis and results more detailed, especially in the analysis of dynamics and transient behavior. Step S32 calculates the amount of substance and fits the kinetic model, applies the ideal gas state equation, calculates the amount of hydrogen substance according to the change of gas volume and pressure, and provides a quantitative comparison between the adsorption characteristics of hydrogen and the quality of the material; uses Langmuir or BET models to fit the data, and determines the hydrogen adsorption rate of the material by analyzing the adsorption isotherm, thereby obtaining the characteristics of the adsorption process. Significance: By calculating the amount of substance, the hydrogen adsorption capacity is quantified, making it possible to compare different materials and promoting the selection of hydrogen storage materials with superior performance; the application of kinetic models allows us to deeply understand the mechanism and characteristics of hydrogen adsorption, clarify the adsorption kinetic behavior of materials, and then guide the optimization and design of materials. Step S33 Drawing analysis and key parameter extraction, by drawing the relationship curve between the adsorption amount of hydrogen on the hydrogen storage material (y-axis) and time (x-axis), the time dependence of hydrogen adsorption is intuitively displayed, which is convenient for observing the dynamic behavior of the adsorption process; key parameters are extracted from the drawn curve, such as the initial adsorption rate, equilibrium adsorption amount and dynamic equilibrium time, and important kinetic parameters such as the adsorption rate constant and diffusion coefficient are calculated. Significance: The hydrogen adsorption kinetic curve provides a visualization tool for evaluating and comparing the performance of hydrogen storage materials, making the hydrogen adsorption capacity of different materials more intuitive; by analyzing the key parameters, we can have a deeper understanding of the adsorption rate and its influencing factors, provide a theoretical basis for the design and development of new materials, and promote the further development of hydrogen storage technology.
[0151] In summary, the entire process of calculating and evaluating the hydrogen storage kinetic performance of the material in this embodiment systematically reveals the adsorption behavior and kinetic characteristics of hydrogen in hydrogen storage materials through real-time data recording, amount of substance calculation, kinetic model fitting and curve analysis. It provides strong support for material application and scientific and technological progress. Such a methodology provides a comprehensive and systematic perspective for the research and application of hydrogen storage materials, allowing future hydrogen storage technology to develop in a more efficient and sustainable direction.
[0152] Furthermore, the process of obtaining the characteristics of the adsorption process in step S32 specifically includes the following steps:
[0153] Step S321: Obtain the data of hydrogen adsorption and corresponding time. Establish a structured data table, including time point, corresponding hydrogen pressure, flow rate, hydrogen adsorption and other information; perform preliminary analysis on the obtained data and draw a curve of hydrogen adsorption changing with time;
[0154] Step S322: Select a fitting tool and use a nonlinear least squares method to minimize the error between the estimated model and the experimental data; input the experimental data and select a model equation;
[0155] Step S323: Check the degree of fit between the fitting curve and the actual data, output the key parameters of the fitting, and calculate the goodness of fit. A value close to 1 indicates that the model predicts the adsorption behavior.
[0156] Preferably, in step S321 of this embodiment, data structuring and preliminary analysis are carried out, and the hydrogen pressure, flow rate and adsorption amount at each time point in the hydrogen adsorption experiment are orderly organized by establishing a structured data table. This structured processing is helpful for subsequent data analysis and model fitting; the relationship between hydrogen adsorption amount and time is preliminarily analyzed, and a change curve is drawn, and the visualization graph helps to identify the trend and characteristics of the adsorption process. Significance: It provides a clear data basis for subsequent analysis, ensures the integrity and readability of the data, and enables researchers to use these data efficiently for further analysis; through visualization, it is possible to intuitively analyze the adsorption dynamics of hydrogen, quickly identify different stages such as the initial stage of adsorption, rapid adsorption, and equilibrium state, and provide a basis for model selection, so that researchers can select a suitable fitting model. Step S322 selects fitting tools and data input, selects suitable fitting tools (such as Excel, Matlab, Python, etc.), and provides technical support for the fitting process through the nonlinear least squares method in the tool; inputs the structured data into the selected fitting software, selects the corresponding model equation (such as Langmuir or BET model), and facilitates parameter estimation. Significance: Various fitting tools have rich functions and flexibility, which make the data processing process well standardized, helping to improve efficiency and reliability of results; accurately selecting and inputting model equations makes the fitting process targeted at the characteristics of experimental data, ensuring the reasonable estimation of subsequent parameters, thereby improving the scientific nature of the results. Step S323 Analysis and evaluation of fitting results, check the degree of fit between the fitting curve and the actual data, output key fitting parameters (such as maximum adsorption amount, equilibrium constant), and calculate the goodness of fit (such as R 2 value); the degree of suitability of the model to the experimental data is judged according to the goodness of fit value, R 2A value close to 1 means that the model can effectively predict the adsorption behavior. Significance: By checking the matching degree between the fitted data and the actual experimental data, the validity of the selected model can be verified, providing a basis for the scientific nature of the model; if the model cannot fit the data well, it may be necessary to re-evaluate the model or consider more complex adsorption mechanisms; the key parameters of the output provide a quantitative basis for understanding the specific characteristics of the adsorption process, such as analyzing the adsorption capacity and kinetic characteristics of the material, thereby providing a direct basis for optimizing the material properties and applications.
[0157] In summary, this embodiment together constitutes a comprehensive analysis of the characteristics of the hydrogen adsorption process. The structuring and visualization of data makes the processing and understanding of information more convenient, the selection of appropriate fitting tools and models ensures the reliability of the results, and by evaluating the fitting results, researchers can have a deeper understanding of the hydrogen adsorption characteristics. The whole process not only improves the systematicness and rigor of the research, but also provides a new direction and foundation for future material optimization and application.
[0158] like Figure 5 As shown, this embodiment also provides an embodiment of a solid hydrogen storage material hydrogen storage performance calculation and evaluation system. In this embodiment, the solid hydrogen storage material hydrogen storage performance calculation and evaluation system is applied to the solid hydrogen storage material hydrogen storage performance calculation and evaluation method in the above embodiment. The solid hydrogen storage material hydrogen storage performance calculation and evaluation system includes a performance analysis module 1, a performance calculation module 2 and a performance evaluation module 3 which are electrically connected in sequence;
[0159] Among them, the performance analysis module 1 is used to analyze the mechanical properties, electronic distribution, thermal conductivity and thermal stability of the designed material itself by constructing a material microscopic model using the functional density theory (DFT) and molecular dynamics (MD) methods; the performance calculation module 2 is used to calculate the hydrogen adsorption performance of the newly designed hydrogen storage material by calculating the adsorption state and adsorption energy of hydrogen molecules on the hydrogen storage material and the amount of hydrogen adsorbed by the material at different pressures and temperatures; the performance evaluation module 3 is used to draw the hydrogen adsorption kinetic curve of the solid-state hydrogen storage material to calculate and evaluate the hydrogen storage kinetic performance of the material.
[0160] Preferably, the performance analysis module 1 of this embodiment uses DFT and MD methods. The performance analysis module can construct a microscopic model of the material. The process of deeply understanding the structure and properties of the material is the basis for the design of hydrogen storage materials. By analyzing the mechanical properties, electronic distribution, thermal conductivity and thermal stability of the material, not only can the physical properties of the material under different environments be obtained, but also the stability and applicability of the material can be evaluated. Detailed quantitative data is provided for subsequent modules to support more accurate performance calculations. Detailed performance analysis is an important basis for determining the suitability of materials. Practical significance: By obtaining the basic physical and chemical properties of the material, this module can speed up the screening and development process of new materials, reduce the need for blind experiments, and improve the overall R&D efficiency. An in-depth understanding of the basic properties of the material helps to promote the optimization design of new materials and ensure their effectiveness and safety in hydrogen storage / application. The performance calculation module 2 calculates the adsorption state and adsorption energy of hydrogen molecules on the hydrogen storage material, obtains the interaction parameters between hydrogen and the material, and deeply understands the adsorption capacity of the material. The calculation of hydrogen adsorption at different pressures and temperatures can evaluate the hydrogen adsorption performance of the material under actual operating conditions, which is crucial for practical applications. The data provided provides key parameters for the subsequent dynamic performance evaluation module to ensure a comprehensive understanding of the hydrogen adsorption performance. Practical significance: It provides quantitative standards for material screening, helps researchers select the best hydrogen storage materials according to specific conditions, and helps improve the actual application efficiency of hydrogen storage; by systematically calculating the hydrogen adsorption performance, it promotes in-depth research on new hydrogen storage materials and promotes scientific progress. Performance evaluation module 3 draws hydrogen adsorption kinetic curves, presents the dynamic characteristics of hydrogen adsorption and desorption processes of hydrogen storage materials, and provides intuitive visual information; calculates and evaluates the hydrogen storage kinetic performance of materials, including adsorption rate, diffusion coefficient, etc., to provide the necessary quantitative analysis for understanding the transport behavior of hydrogen in materials; realizes a comprehensive evaluation of hydrogen storage materials in terms of kinetics, and ensures that the final selected materials exhibit excellent hydrogen storage capacity under both transient and steady-state conditions. Practical significance: Through comprehensive kinetic performance evaluation, it ensures that the selected hydrogen storage materials have good reaction speed in practical applications, which improves the reliability of industrial applications; the dynamic evaluation results can guide subsequent material improvements and technological innovations, and promote the overall progress of hydrogen storage technology.
[0161] In summary, the performance analysis module of this embodiment provides basic data support and material property analysis, the performance calculation module optimizes it into specific hydrogen storage performance indicators, and the performance evaluation module ensures the actual performance and application feasibility of the material through dynamic analysis. The systematic structure coordinates the theoretical research and practical application of materials, and by providing a comprehensive and detailed hydrogen storage performance evaluation, it lays a solid foundation for the future development of hydrogen energy technology and material innovation, and helps promote the widespread application of renewable energy.
[0162] like Figure 6 As shown, this embodiment provides an embodiment of an electronic device. In this embodiment, the electronic device 4 includes a processor 41 and a memory 42 coupled to the processor 41.
[0163] The memory 42 stores program instructions for implementing the method for calculating and evaluating the hydrogen storage performance of the solid hydrogen storage material according to any of the above-mentioned embodiments.
[0164] The processor 41 is used to execute program instructions stored in the memory 42 to calculate and evaluate the hydrogen storage performance of the solid hydrogen storage material.
[0165] The processor 41 may also be referred to as a CPU (Central Processing Unit). The processor 41 may be an integrated circuit chip having signal processing capabilities. The processor 41 may also be a general-purpose processor, a digital signal processor (DSP), an application-specific integrated circuit (ASIC), a field programmable gate array (FPGA) or other programmable logic devices, discrete gate or transistor logic devices, discrete hardware components. The general-purpose processor may be a microprocessor or the processor may also be any conventional processor, etc.
[0166] Further, Figure 7 The schematic diagram of the structure of the storage medium of an embodiment of the present application is that the storage medium 5 of the embodiment of the present application stores program instructions 51 that can implement all the above methods, wherein the program instructions 51 can be stored in the above storage medium in the form of a software product, including several instructions for enabling a computer device (which can be a personal computer, server, or network device, etc.) or a processor to execute all or part of the steps of the methods described in each embodiment of the present application. The aforementioned storage medium includes: various media that can store program codes, such as a USB flash drive, a mobile hard disk, a read-only memory (ROM), a random access memory (RAM), a magnetic disk or an optical disk, or terminal devices such as a computer, a server, a mobile phone, and a tablet.
[0167] Calculation and evaluation of hydrogen storage performance of Na-modified low-dimensional porous graphene
[0168] Figure 8 The structure of the unit cell model of sodium-modified nitrided porous graphene. (a), (b) and (c) are porous graphite, single and double Na-modified porous graphene, respectively.
[0169] The present invention is a method for calculating and evaluating the hydrogen storage performance of a solid-state hydrogen storage material, which includes theoretical calculation and evaluation of the electronic properties, hydrogen adsorption properties, thermal conductivity, thermal stability and hydrogen kinetic properties of the solid-state hydrogen storage material. Figure 8Figure 1 is a model diagram of nitrided porous graphene before and after Na modification. The following model will be used as an example to illustrate the specific implementation of the present invention. The calculation software and methods used in the following examples are obtained from open source channels unless otherwise specified.
[0170] Fig. 9 The DFT method is used to calculate the electronic band structure diagram in the energy range of -5 to 5 eV using the VASP software package, which can be used to analyze the electronic characteristics of the present invention. Fig. 9 It can be seen that the electronic band gaps of the three materials are Eg1 = 1.65eV, Eg2 = 1.52eV and Eg3 = 1.22eV (the orange part in the figure). This shows that when sodium atoms are modified on the surface of nitrided porous graphene, the electronic band gap of the material will be reduced, and electrons will be more easily excited from the valence band to the conduction band to participate in heat transport, thus promoting the thermal conductivity of the material. The more sodium atoms are modified, the more obvious this effect is. Figure 2 It can also be seen that the band gap positions of C2N, C2N+Na and C2N+Na are constantly moving down, and the work function is constantly increasing. This shows that as the number of sodium atoms modified gradually increases, the binding effect of electrons in the material becomes stronger, electron emission becomes difficult, and it is not conducive to the thermal conductivity of the material. In summary, it is necessary to further calculate the electronic thermal conductivity of the material to clarify which effect is dominant in the competition between the band gap reduction brought about by sodium metal modification and the increase in work function in the thermal conductivity of the material. In addition, Figure 2 As shown in the figure, there is no energy band passing through the Fermi level of nitrided porous graphene (orange dotted line), while the two sodium-modified nitrided porous graphenes have energy bands passing through the Fermi level. This shows that nitrided porous graphene has semiconductor properties, while sodium-modified nitrided porous graphene has metallic properties. Therefore, when calculating electronic properties, the electron relaxation time of C2N+Na and C2N+2Na is taken as 10fs.
[0171] The electronic properties of the material can also be determined by Fig.10 The charge difference density diagram shown in Figure 1 is used for analysis. The charge difference density diagram can be used to qualitatively analyze the electron transfer characteristics between atoms in the material. From the results in the figure, it can be seen that there is charge transfer between Na atoms and N atoms, so there is a strong interaction between Na atoms and N atoms.
[0172] Table 1 Bader charge and binding energy of Na atoms when one or two Na atoms are modified into nitrided porous graphene
[0173] Single Na modification Two Na modifications <![CDATA[Q Bader,Na (e)]]> +0.78 +0.74 / 0.71 <![CDATA[avE bind,Na (eV)]]> 4.83 2.65
[0174] The electronic properties of the material can also be quantitatively analyzed through the Bader charge and binding energy results in Table 1. From the results in Table 1, we can quantitatively see the amount of charge transferred from Na atoms to N atoms. The adsorption capacity of Na atoms on the surface of the material can be quantitatively analyzed through the calculation results of binding energy. From the results in the table, it can be seen that whether it is a single or double Na modification, its binding energy is greater than 0.5eV, which is a chemical adsorption form and can be stably adsorbed on the surface of the material.
[0175] The hydrogen adsorption performance of the material can be analyzed by the charge difference density diagram when hydrogen is adsorbed on the surface of the material. The calculation results are as follows: Fig.11 As shown in the figure, it can be seen from the results that when a single Na is modified, the adsorption of hydrogen molecules on the surface of the material is more dispersed, and the polarization effect of hydrogen analysis is smaller. When two Na are modified, the distribution of hydrogen molecules on the surface of the material is more concentrated, and the polarization effect of hydrogen molecules is more obvious. Therefore, it is believed that the nitrided porous graphene modified with two Na has a stronger adsorption effect on hydrogen molecules.
[0176] The thermal conductivity of materials includes electronic thermal conductivity and phonon thermal conductivity. Electronic thermal conductivity is calculated by combining VASP and BoltzTraP2 software. Phonon thermal conductivity is calculated by using VASP and Alamode software.
[0177] To analyze electronic thermal conductivity, we must first calculate the electronic transport properties of the material, such as Fig.12 The ratio of the conductivity of each material to the electron relaxation time is calculated by BoltzTraP2, and then multiplied by the electron relaxation time of the corresponding material to obtain the variation characteristics of the material conductivity and power factor with the carrier concentration in the material, as shown in Fig.12 shown. Fig.12 (a) shows that the conductivity of nitrided porous graphene increases with the increase of carrier concentration. At the same time, the conductivity of the two sodium-modified nitrided porous graphene changes very little at the beginning and then increases slowly with the increase of carrier concentration. Since the electrical conductivity is proportional to the electronic thermal conductivity, it can be determined that the change trend of the electronic thermal conductivity of the material with the carrier concentration is similar to that of the electrical conductivity.
[0178] Furthermore, the electronic thermal conductivity of the material is calculated as Fig.13 As shown in the figure, the electronic thermal conductivity of nitrided porous graphene increases significantly with the increase of carrier concentration, while the electronic thermal conductivity of the two sodium-modified nitrided porous graphene increases gradually, which is similar to the change trend of electrical conductivity. At the optimal carrier concentration, the electronic thermal conductivity of nitrided porous graphene, single and double Na atoms modified are 1.48 Wm -1 K -1 、1.46Wm -1 K -1and 1.33Wm - 1 K -1 The results showed that the electronic thermal conductivity of the material decreased slightly after the addition of sodium metal.
[0179] To analyze the phonon thermal conductivity, we must first calculate the phonon dispersion relation of the material. The results are as follows: Fig.14 As shown in the figure. From the results, it can be seen that sodium atom modification will cause three major changes in the phonon properties of the material. First, high-frequency optical phonons (yellow solid line frame) will be red-shifted, and this phenomenon becomes more obvious with the increase in the number of sodium atoms. This phenomenon causes the high-frequency phonons to soften, which in turn reduces the high-frequency phonon group velocity, thereby reducing the lattice thermal conductivity. In addition, some new phonon branches are generated in the low-frequency range. Although these new phonon branches contribute to the transfer of heat, their contribution to thermal conductivity is extremely limited due to their small phonon branch slope and low group velocity. Finally, low-frequency acoustic phonons exhibit a softening effect. In solid materials, acoustic phonons play an important role in heat transfer. Therefore, the softening of acoustic phonons will lead to a significant decrease in the lattice thermal conductivity of the material.
[0180] Furthermore, in order to analyze the phonon thermal conductivity, the phonon relaxation time and group velocity of the material were calculated. The results are as follows: Fig.15 shown. Fig.15 (a) shows that the phonon relaxation time of nitrided porous graphene is mainly concentrated in the range of 0.1-10ps. In the low-frequency range (<10THz), the phonon relaxation time of nitrided porous graphene, single and double Na atom decoration decreases in turn. This shows that adding metallic sodium decoration to nitrided porous graphene will lead to low-frequency phonon scattering inside the material, thereby shortening the phonon relaxation time. Fig.15 As shown in (b), when the frequency is lower than 10 THz, the phonon group velocities of nitrided porous graphene, single and double Na atom modified graphene show a decreasing trend, resulting in a decrease in lattice thermal conductivity.
[0181] Furthermore, the phonon thermal conductivity of the material is calculated to quantitatively analyze the phonon thermal conductivity of the material. Fig. 9 The lattice thermal conductivity of sodium-modified nitrided porous graphene is given. At room temperature (300K), the lattice thermal conductivity of nitrided porous graphene is 17.88 Wm -1 K -1 The thermal conductivity of single and double Na-modified nitrided porous graphene is 6.02 Wm -1 K -1 and 3.48Wm - 1 K -1. At the same temperature, the lattice thermal conductivity of nitrided porous graphene, single and double Na atom modified graphene decreases in turn. With the increase of temperature, the thermal conductivity of nitrided porous graphene decreases more obviously, while the thermal conductivity of sodium-modified nitrided porous graphene decreases more gently, among which the lattice thermal conductivity of two Na-modified nitrided porous graphene remains almost unchanged. Therefore, it can be concluded that the addition of sodium metal will reduce the lattice thermal conductivity of the material and reduce its sensitivity to temperature changes. Analysis of phonon properties shows that sodium atoms scatter phonons in the material, thereby reducing its phonon relaxation time. The simultaneous reduction of phonon relaxation time and group velocity leads to a significant decrease in the lattice thermal conductivity of the material, and the sensitivity of the lattice thermal conductivity of the material to temperature is reduced.
[0182] The above analysis shows that the modification of metal Na will increase the hydrogen storage capacity of the material, but at the same time it will also reduce the thermal conductivity of the material, thereby reducing the hydrogen adsorption kinetics of the material. Furthermore, the hydrogen adsorption kinetics of the material are calculated and analyzed using the MD method.
[0183] The hydrogen adsorption kinetic curve includes hydrogen adsorption isotherm, isobar, adsorption / release rate, etc. Adsorption kinetics mainly studies the diffusion properties of hydrogen in hydrogen storage materials. Since the temperature of the system needs to be regulated during the charging / discharging process of solid hydrogen storage materials, the thermal conductivity of the material has a great influence on the hydrogen adsorption kinetic characteristics of the hydrogen storage material.
[0184] In the several embodiments provided by the present invention, it should be understood that the disclosed systems, devices and methods can be implemented in other ways. For example, the device embodiments described above are only schematic, for example, the division of units is only a logical function division, and there may be other division methods in actual implementation, such as multiple units or components can be combined or integrated into another system, or some features can be ignored or not executed. Another point is that the mutual coupling or direct coupling or communication connection shown or discussed can be an indirect coupling or communication connection through some interfaces, devices or units, which can be electrical, mechanical or other forms.
[0185] In addition, each functional unit in each embodiment of the present invention may be integrated into one processing unit, or each unit may exist physically separately, or two or more units may be integrated into one unit. The above integrated unit may be implemented in the form of hardware or in the form of software functional units. The above is only an implementation mode of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly used in other related technical fields, is also included in the patent protection scope of the present invention.
[0186] The specific implementation methods of the invention are described in detail above, but they are only examples, and the invention is not limited to the specific implementation methods described above. For those skilled in the art, any equivalent modification or substitution of the invention is also within the scope of the invention, therefore, the equalization, modification, improvement, etc. made without departing from the spirit and principle of the invention should be included in the scope of the invention.
Claims
1. A method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material, characterized in that: The method for calculating and evaluating the hydrogen storage performance of the solid hydrogen storage material comprises: By using functional density theory and molecular dynamics, we build a material microscopic model to analyze and design the mechanical properties, electron distribution, thermal conductivity and thermal stability of the material itself. Calculate the hydrogen adsorption performance of the newly designed hydrogen storage material by calculating the adsorption state, adsorption energy and hydrogen adsorption amount of the material at different pressures and temperatures of the hydrogen molecules on the hydrogen storage material; Draw the hydrogen adsorption kinetic curve of solid-state hydrogen storage materials to calculate and evaluate the hydrogen storage kinetic performance of the materials.
2. The method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material according to claim 1, characterized in that: Material micro-model analysis process, including: Use applied functional density theory to perform geometric optimization, determine the optimal lattice structure of the material, and use exchange-correlation functional to calculate the optimized structure of the material; obtain the electron density distribution of the optimized structure through calculation, and extract the electronic state, band structure and Fermi level information; analyze the conductive properties of the material, and determine its conductive and insulating properties through state density diagrams and band diagrams; use Bader charge analysis to evaluate charge transfer and localization phenomena, and obtain the chemical properties and reaction behaviors of the material; for the interaction potential between materials, select according to the characteristics of the material and the nature of the interaction; Use the optimal geometric structure obtained by applying functional density theory as the initial configuration of molecular dynamics simulation; set temperature, pressure and time step parameters; run molecular dynamics simulation at different temperatures and pressures to obtain the thermal behavior, phase change process and mechanical response of the material; test the adsorption and diffusion behavior of gas molecules on the surface of the material to obtain dynamic information; apply external stress, generate stress-strain curves, and analyze the elastic modulus, yield strength and fracture behavior of the material; analyze the relative motion between atoms, extract the information of the displacement field, and obtain the changes in the mechanical properties of the material; Use non-equilibrium molecular dynamics to analyze the thermal conductivity of materials at different temperatures; calculate lattice vibration and phonon heat conduction to evaluate the impact of thermal motion at the atomic level on macroscopic thermal conductivity; apply repeated thermal cycles in molecular dynamics to obtain the stability and deformation of materials in high-temperature environments; after the material reaches thermal equilibrium, evaluate its corresponding properties in the thermally excited state and identify potential phase transitions or degradation mechanisms.
3. The method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material according to claim 2, characterized in that: The process of optimizing the structure of materials selected for exchange-correlation functional calculations includes: Extract the initial structure of the material using the database, including atomic positions and symmetries; set the geometry optimization parameters in the calculation software, and set the force and energy convergence criteria; start the calculation and run the geometry optimization; Use the optimized crystal structure to perform self-consistent field calculations to obtain the electron density distribution. In the file output, view and analyze the electron density distribution diagram; select the k-point grid to calculate the energy band trend along a specific high-symmetry direction; generate the energy band diagram and state density diagram to analyze the filling state of each energy level; obtain the Fermi level position from the state density calculation and mark the Fermi level position in the energy band diagram; Determine the properties of metals, semiconductors or insulators by the shape of the state density diagram; analyze the width of the band gap, calculate the conductivity and estimate the prediction model; use Bader charge analysis to calculate the charge value of each atom to ensure the correct distribution of local charges, present the charge distribution through visualization tools, and analyze which atoms or compounds receive or lose electrons; combine Bader results to analyze the degree of localization of electrons between different atoms and determine possible reaction active sites.
4. The method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material according to claim 1, characterized in that: The process of calculating the hydrogen adsorption performance of newly designed hydrogen storage materials includes: After obtaining a stable structure, a molecular dynamics simulation is performed, and the initial temperature and pressure are set; the molecular dynamics simulation is run to obtain the kinetic stability and thermal stability data of the material, and the selected structure of the material at different temperatures is obtained; Add hydrogen molecules to the optimized hydrogen storage material model, calculate different adsorption sites on the surface, vacancies or three-dimensional channels, calculate the energy of each site, identify the optimal adsorption site, evaluate the hydrogen adsorption energy at different sites, and select the adsorption site by comparing the adsorption energy at different sites; Thermodynamic calculations are performed at different temperatures and pressures to evaluate the amount of hydrogen adsorbed in the material, and adsorption isotherms are used to estimate the adsorption amount under different conditions and quantify the hydrogen adsorption performance of the material.
5. The method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material according to claim 4, characterized in that: The process of obtaining the selected structure of a material at different temperatures includes: Obtain the preliminary crystal structure of the hydrogen storage material and generate a three-dimensional model; perform geometric optimization on the initial structure, use functional density theory methods to calculate, optimize the coordinates of each atom, and obtain the lowest energy configuration; perform molecular dynamics simulation for each target temperature; Describe the interaction between atoms in the material and conduct thermal equilibrium under isobaric conditions at a set initial temperature; after reaching thermal equilibrium, continue to run the simulation to obtain the movement and changes of atoms inside the material; extract atomic coordinate data once and record the system configuration under the current temperature conditions; The collected structural data are analyzed to calculate the atomic displacement, square displacement and average spacing properties of the material at different temperatures. The most stable and representative structures at different temperatures are screened out using the coordination number and distribution between atoms and the energy minimization criterion. The selected stable structures at different temperatures are summarized, visualized and a temperature spectrum is generated.
6. The method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material according to claim 4, characterized in that: The process of identifying the optimal adsorption sites includes: Geometric description is performed on the surface and internal structure of hydrogen storage materials, and different possible hydrogen molecule adsorption sites are depicted using geometric features and spatial symmetry; Synchronously introduce one or more hydrogen molecules into the model of the hydrogen storage material around the differently labeled adsorption sites; dynamically simulate the hydrogen molecules at the different adsorption sites; observe the movement of the hydrogen molecules under set initial conditions and record the interaction with the hydrogen storage material; For each adsorption site, the potential energy relationship is used to calculate the interaction energy between the hydrogen molecule and the material; the relative stability of the hydrogen molecule at each adsorption site is obtained through an energy minimization program; the calculated adsorption energies are compared to identify the site with the lowest energy and mark it as the optimal adsorption site.
7. The method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material according to claim 4, characterized in that: The process of quantifying the hydrogen adsorption performance of a material includes: Using a gas adsorption isotherm measuring device, hydrogen is introduced into the pre-vacuum treated hydrogen storage material, and different hydrogen pressures are gradually applied; at each set pressure, the gas volume change, pressure change and temperature change during the adsorption process are monitored in real time through a range instrument; The ideal gas state equation is used to calculate the amount of gas at a specific pressure, and the amount of hydrogen adsorbed is compared with the mass of the material to calculate the amount of hydrogen adsorbed per gram of material. The corresponding gas adsorption experiments are carried out under different temperature and pressure conditions. The adsorption isotherm model is used to fit the data and extract the thermodynamic parameters in the adsorption isotherm. By calculating the adsorption isotherm and thermodynamic parameters, the maximum adsorption capacity of stored hydrogen and the transfer and release characteristics of the gas within the material are obtained; the adsorption efficiency under different conditions, including the saturated adsorption capacity, kinetic adsorption rate and desorption rate, is recorded and analyzed; the test results are compared with the adsorption performance of the hydrogen storage material.
8. The method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material according to claim 1, characterized in that: The process of calculating and evaluating the hydrogen storage kinetics of materials includes: The pressure sensor and flow meter are used to record the changes in pressure and flow of hydrogen at different time points in real time to form a dynamic monitoring data set; the data collected from the adsorption experiment are processed to calculate the hydrogen adsorption at different time points and record the changes in the amount of hydrogen at each time point; Apply the ideal gas state equation, calculate the amount of substance corresponding to hydrogen adsorption based on the gas volume and pressure changes, and compare it with the material mass; use the acquired data to fit the hydrogen adsorption rate using a kinetic model to obtain the characteristics of the adsorption process; Plot a curve of the relationship between the amount of hydrogen adsorbed on the hydrogen storage material and time on the coordinate scale to demonstrate the time dependence of hydrogen adsorption; extract key parameters from the plotted curve; calculate important kinetic parameters such as the hydrogen adsorption rate constant and diffusion coefficient to evaluate the hydrogen adsorption kinetic performance of the material.
9. The method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material according to claim 8, characterized in that: The process of characterizing the adsorption process includes: The data of hydrogen adsorption and corresponding time are obtained to establish a structured data table, including time point, corresponding hydrogen pressure, flow rate, and hydrogen adsorption information; preliminary analysis is performed on the obtained data to draw a curve of hydrogen adsorption changing with time; Select the fitting tool and use nonlinear least squares to minimize the error between the estimated model and the experimental data; input the experimental data and select the model equation; Check the fit between the fitted curve and the actual data, output the key parameters of the fit, and calculate the goodness of fit. A value close to 1 indicates that the model predicts the adsorption behavior.
10. A system for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material, which is applied to the method for calculating and evaluating the hydrogen storage performance of a solid hydrogen storage material as claimed in any one of claims 1 to 9, characterized in that: The solid hydrogen storage material hydrogen storage performance calculation and evaluation system comprises: Performance analysis module, which uses functional density theory and molecular dynamics to build a material microscopic model to analyze the mechanical properties, electronic distribution, thermal conductivity and thermal stability of the designed material itself; Performance calculation module, used to calculate the hydrogen adsorption performance of the newly designed hydrogen storage material by calculating the adsorption state and adsorption energy of hydrogen molecules on the hydrogen storage material and the amount of hydrogen adsorbed by the material at different pressures and temperatures; The performance evaluation module is used to draw the hydrogen adsorption kinetic curve of solid-state hydrogen storage materials to calculate and evaluate the hydrogen storage kinetic performance of the materials.
Citation Information
Patent Citations
Preparation method of amino metal solid hydrogen storage material and solid hydrogen storage material
CN112758890A
Additive capable of improving hydrogen storage performance of lithium magnesium nitrogen hydride as well as preparation and application of additive
CN114684783A
Membrane type hydrogen storage material, preparation method and application
CN116924325A
Method for representing catalytic material and / or adsorbate
CN110111853A
Adsorbate gas adsorption phase density model construction and absolute adsorption capacity calculation method
CN110534161A
Cited By
Intelligent hydrogen storage management system
CN119900923A
Method and system for generating three-dimensional pore atom model based on preset target pore parameters
CN120600132A
A method and system for generating a three-dimensional pore atom model based on a preset target pore parameter
CN120600132B